(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The Lusitanian text of Cabeço das Fráguas follows an evident and clearly intentional symmetry between the two series of declared elements: the animal offerings and the receiving deities. Assuming the theonyms to be in the dative case, the traditional interpretation of this epigraph called for the existence of singular dat. in -a of the first declension in this linguistic context. But this axiom was based on fragile evidences and was refuted by Untermann and others who, however, offered alternatives that lacked solidity themselves. An attempted compromise by the author of the present paper later proved to be likewise erroneous. Now, reviewing the in- ternal features of the text and the specificities of the sanctuary, a radically different proposition is presented, approaching the epigraph of Fráguas as an invocatio and considering the theonyms to be necessarily written, without exception, in the vocative case.